Central Pontine Myelinolysis with Minimal Hyponatremia in the Setting of AIDS - Joseph M. Carrington; Galo Sanchez; Jennifer L. Berkeley (Case Reports in Neurological Medicine)
Central pontine myelinolysis (CPM) is classically attributed to overly rapid correction of profound hyponatremia. However, there are case reports of this disease in the setting of normal serum sodium or minimal hyponatremia. These cases have been hypothesized to be secondary to other metabolic disturbances such as hyperglycemia or hypophosphatemia. Eunatremic CPM has also been described in patients with advanced acquired immune deficiency syndrome (AIDS). The mortality risk in this special population is significantly higher than those with hyponatremia-associated CPM, but the mechanisms are unclear. We discuss a case of a man with AIDS who developed CPM with minimal hyponatremia and no other metabolic disturbances. Common variables within this population, such as hypoalbuminemia and lymphoma, are discussed as potential factors contributing to the pathophysiology. Reporting these atypical cases is crucial to our understanding of how to prevent future cases.